Photocatalytic Degradation of Methylene Blue by Titanium Dioxide: Experimental and Modeling Study - Xu, Chen; Rangaiah, G. P; Zhao, X. S (Industrial & engineering chemistry research, 2014)
The application of semiconductors in water treatment via photocatalysis of various pollutants has attracted much attention from researchers. In this work, photocatalytic degradation of methylene blue by P25 titanium dioxide was studied experimentally and then via modeling. The effects of lamp choice, concentration of catalyst, and methylene blue were analyzed. Desorption of methylene blue at the start of light radiation was observed, and analyzed in detail for the first time. Both desorption and degradation processes were modeled, and experimental data was fitted to a pseudo-first-order model with sufficient accuracy. The effects of catalyst and initial dye concentration on reaction rate constants were discussed.